Räume und Identitaten : Stiftsdamen und Damenstifte in Ausburg und Edelstetten im 18. Jahrhundert - Schiersner, Dietmar (Studien zur Germania sacra (Berlin, Germany), 2014)
What was the nature of life - and death - in an 18th century Catholic convent? From an anthropological and cultural perspective, Dietmar Schiersner examines the lives of the sisters in sickness and in health, their clothing, living spaces and spaces of the imagination (reading, writing, and music-making), and the rhythms of their lives: days, years, life stages, generational conflicts, the hour of death, eternity, and institutional memorials.